Management control systems design of Malaysian Research and Development Units - Khairul Naziya Kasim,; Rozita Amiruddin,; Sofiah Md. Auzair, (FEP, 2012)
The nucleus for any high income economy is its successful innovation agenda. This gives rise to the importance of wellmanaged research and development (R&D) activities for the economy. To address this issue, the study aims to understand the relationships between task uncertainty and Management Control Systems (MCS) in R&D units of Malaysian manufacturing firms. Specifically, the relationship between two dimensions of task uncertainty, task variability and task analyzability; and four characteristic of MCS are investigated. The MCS characteristics were conceptualized using the framework that includes the MCS degree of formalization; degree of tightness; degree of influence and participation involved; and the scope of information used. This study suggests fit between task uncertainty and MCS will enhance R&D performance. Survey questionnaires were administered to managers of R&D units in 61 manufacturing companies operating in Malaysia. Using moderated regression analysis, the results showed that high unit performance was reported when there was interaction (1) between task non-analyzability and controls formalization, (2) between task variability and influence and participation of subordinates in control process, and (3) between task variability and scope of information. These findings suggest that the two dimensions of task uncertainty affect different MCS characteristics in a different manner to produce high R&D unit performance. This study provides important implication for management as it involves a greater understanding of the governance structure of the R&D unit. The finding suggests that the design of the MCS needs to take into account information gaps among employees, which contribute to uncertainty when performing their work tasks.